Cinética de incorporación de vitaminas liposolubles y antioxidantes en carne de “Carpa Herbívora” (Ctenopharyngodon idella) - Montenegro, Luciano Federico; Perez, Carolina Daiana; Rossetti, Luciana; Descalzo, Adriana Maria (Asociación Argentina de Producción Animal, 2022)
The incorporation of antioxidant fat-soluble vitamins to the meat of the fish can prevent the oxidation of the lipids that compose it since their stability depends on the balance between antioxidant components and pro-oxidants. The use of pastures in food can increase the levels of polyunsaturated fatty acids long chain (PUFAs) in meat and compensate for the higher oxidative vulnerability by providing natural antioxidants. The aim of the trial was to study the kinetics of incorporation of fat-soluble vitamins and antioxidants in meat from fry of C. idella fed with two diets contrasting. It was found that fat-soluble vitamins present in the diet accumulate in the meat of the fingerlings of C. idella in a sustained manner over time. Therefore, by feeding sources rich in these compounds, such as pastures, can increase the vitamin content significantly fact that, could improve the antioxidant status of meat.